International disease epidemics and the shadow economy - Berdiev, Aziz N.,Goel, Rajeev K.,Saunoris, James W. (CESifo, Center for Economic Studies & Ifo Institute, 2020)
Adding to the emerging body of research related to the current coronavirus crisis, this paper studies the impact of disease epidemics on the worldwide prevalence of the shadow or the underground economy. The informal sector undermines compliance with government regulations and lowers tax collections. Our main hypothesis is that epidemics positively impacts the spread of the shadow economy. Using data on nearly 130 nations and nesting the empirical analysis in the broader literature on the drivers of the shadow sector, we find that both the incidence and the intensity of epidemics positively and significantly contribute to the spread of the underground sector. Numerically, a ten percent increase in the intensity of epidemics leads to an increase in the prevalence of the shadow economy by about 2.1 percent. These findings about the spillovers from epidemics have implications for economic policies in the current times of coronavirus.
10419/223497
Keywords: Graue Literatur; shadow economy; epidemics; COVID-19; government; economic development